The increasing importance of grapevine trunk diseases - Kovács, Cs.; Sándor, E. (International Journal of Horticultural Science, 2016)
Grapevine trunk diseases (GTDs) are destroying the woody parts of the plants, resulting decline or dieback of the grapevine. More detailed research of the GTD began in 1950s, when Hewitt et al. (1957) observed that specific symptoms cannot be detected on the diseased trunks every year. Latest results have also proved that abiotic factors affect the appearance and the severity of the disease. Moreover several pathogenic fungi may play role as causative agents (Bertsch et al., 2013). Eutypa, Botryosphaeria, Phomopsis dieback, esca disease complex, and Petri disease are considered the major GTDs, where a variety of pathogens attack the woody perennial organs of the vine and ultimately lead to the death of the plant (Lehoczky, 1974; Larignon & Dubos, 1997; Rolshausen et al. 2010; Kotze et al., 2011; Bertsch et al., 2013; Fontaine et al., 2015). The GTD incidence has been reported to be increased during the last decades (Úrbez-Torres et al., 2014). The esca incidence has reached 60% to 80% in some old vineyards in southern Italy (Pollastro et al., 2000; Surico et al., 2000; Calzarano & Di Marco, 2007). The disease incidence of the esca was reported to be increased from 1.83% to almost 13%, between 2003 and 2007 in Hungary (Dula, 2011). There was detected a five times increase in the GTD disease incidence in the Tokaj Wine Region, Hungary between 2014 and 2016 (Bihari et al, 2016).